PENGARUH LITERASI KEUANGAN DAN FINTECH PEER TO PEER LENDING TERHADAP KEPUTUSAN PENGGUNAAN SHOPEEPAYLATER : Studi Kasus Pada Mahasiswa Angkatan 2019-2022 di Sekolah Tinggi Ilmu Administrasi Malang - Agustiningtias, Eka; Ayu Lusita, Yeri Dwi; Setiyowati, Arie Ika (JOURNAL AKSES STIA MALANG, 2025)
This research aims to analyze the influence of financial literacy and fintech peer to peer lending on the decision to use Shopee PayLater. The population in this study was all 71 students at the School of Administration (STIA) Malang class 2019-2022 because there were less than 100 respondents. And the sample that meets the requirements is only 63 respondents. This study used a saturated sample.The results of the f test show that the variables influence Financial Literacy and Fintech Peer to Peer Lending simultaneously and have a significant influence on the variable Decision to Use Shopee Paylater with the result being Fcount > Ftable = 10,435 > 3.15 and a significance value of 0.02 < 0.05, which means the hypothesis of this research accept H1. From the analysis of the Coefficient of Determination (R2) it shows that the R score for this research is 0.705 or it can be explained that the independent variable model contributes to the dependent variable by 70.5% while the remaining 29.5% is explained by other variable models outside this research.